Rhetoric Strategy in Speech Practice for Da'wah Management Students Semester 5 UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan - Sultoni Matondang, Ahmad; Dianto, Icol; Kahpi, Mhd. Latip (Sekolah Tinggi Agama Islam Kuningan, 2026)
Backround: This study analyzes rhetorical strategies in the speech practices of fifth-semester students of Da'wah Management at UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan.Objective: The background of the study stems from the importance of rhetorical competence as a core skill of professional da'wah communicators in facing the increasingly complex and heterogeneous dynamics of contemporary public communication. The purpose of the study is to identify the implementation of students' rhetorical strategies and their implications for the formation of professional da'wah competence.Method: The study used a qualitative descriptive-interpretive approach with 28 fifth-semester Da'wah Management students as subjects, through participatory observation techniques, in-depth interviews, and documentation of speech practices. Data analysis was conducted thematically following open, axial, and selective coding procedures based on Aristotle's classical rhetorical framework (ethos, pathos, logos) and a contemporary da'wah rhetorical approach.Findings and Implications: The results show that students have implemented the elements of ethos, pathos, and logos with varying levels of mastery, supported by linguistic and nonverbal strategies and message contextualization for academic and social audiences.Conclusion: The implications of the research show that rhetorical strategies contribute significantly to the formation of communication competence, professional self-confidence, ethical awareness, managerial abilities in preaching, and soft skills of students as prospective professional, ethical, and adaptive preaching communicators.